Bowman Layer Onlay Graft for Reducing Fluctuation in Visual Acuity After Previous Radial Keratotomy. Issue 10 (October 2020) - Parker, Jack S.; Dockery, Philip W.; Parker, John S.; Dapena, Isabel; van Dijk, Korine; Melles, Gerrit R. J.
Abstract : Purpose: To describe the clinical outcome of a first patient undergoing Bowman layer (BL) transplantation with an onlay graft to reduce fluctuation in visual acuity and refractive error after previous radial keratotomy (RK) surgery. Methods: In 2018, a 66-year-old woman presented with complaints of long-standing diurnal fluctuation in best-spectacle corrected visual acuity (BSCVA) after RK in 1983. After the removal of host epithelium, a BL graft was positioned onto the host cornea. BSCVA, Scheimpflug-based corneal tomography, and anterior segment optical coherence tomography were evaluated up to 12 months postoperatively. Results: The surgery and postoperative course were uneventful. After surgery, the subjective complaints of visual fluctuation were reduced from 10 to 3 on a scale from 1 to 10. BSCVA (20/40; 0.5) did not change from preoperative to postoperative. Corneal tomography showed an overall central corneal steepening of 5.9 diopters. Biomicroscopy, Scheimpflug imaging, and anterior segment optical coherence tomography showed a completely epithelialized and well-integrated graft, with some minor epithelial remnants located in the preexisting keratotomy incisions. Conclusions: BL onlay grafting may have the potential to manage patients with subjective complaints of diurnal fluctuation in visual acuity after previous RK.